2013
DOI: 10.1002/jbm.a.34860
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐dependent surface endothelialization and biocompatibility of polyurethane noble metal nanocomposites

Abstract: Surface pre-endothelialization is a promising approach to improve the hemocompatibility of implants, medical devices, and artificial organs. To promote the adhesive property of thermoplastic polyurethane (TPU) for endothelial cells (ECs), up to 1 wt % of gold (Au) or platinum (Pt) nanoparticles, fabricated by pulsed laser ablation in polymer solution, were embedded into the polymer matrix. The analysis of these nanocomposites showed a homogenous dispersion of the nanoparticles, with average diameters of 7 nm f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 48 publications
3
36
0
Order By: Relevance
“…As an example, homogeneously distributed silver nanoparticles in TPU are shown in Figure 4E. For noble metals like gold, platinum, silver or copper, pulsed laser ablation in liquid results in metal nanoparticles and no indication of bulk oxidation [40], with plasmon resonance spectra typical for elemental silver and copper nanoparticles and high ion-release capacities [27]. During laser ablation of base metals like magnesium or zinc in organic solvents, partial oxidation of the nanoparticles cannot be excluded, although nanocomposites with elemental magnesium embedded in a polymer have been fabricated recently by this method [41].…”
Section: In Vitro Cytocompatibility and Bacterial Growth Inhibition Omentioning
confidence: 99%
“…As an example, homogeneously distributed silver nanoparticles in TPU are shown in Figure 4E. For noble metals like gold, platinum, silver or copper, pulsed laser ablation in liquid results in metal nanoparticles and no indication of bulk oxidation [40], with plasmon resonance spectra typical for elemental silver and copper nanoparticles and high ion-release capacities [27]. During laser ablation of base metals like magnesium or zinc in organic solvents, partial oxidation of the nanoparticles cannot be excluded, although nanocomposites with elemental magnesium embedded in a polymer have been fabricated recently by this method [41].…”
Section: In Vitro Cytocompatibility and Bacterial Growth Inhibition Omentioning
confidence: 99%
“…A similar cell response occurred on the pure TiO 2 films and the Pt/C-TiO 2 composite films, because the two kinds of films had almost the same characteristics in surface morphology. Better cell adhesion and proliferation for PCT-4 films may be attributed to the dose-dependent effect of Pt [26] coupled with more graphite amounts which was demonstrated to strongly stimulate cell adhesion and proliferation [27,28]. Interestingly, recent study also reported that filopodia of osteoblast cells inclined to move towards and got anchored by graphene, which in turn facilitated the spreading and subsequent proliferation of the cells [29].…”
Section: Cell Adhesion and Proliferation On Pt/c-tio 2 Composite Filmsmentioning
confidence: 86%
“…4 a). Note that Hess et al [57] achieved fivefold improvement of nanocomposite biofunctionality already at an AuNP doping level of 0.1 wt %. Fig.…”
Section: Composite Synthesismentioning
confidence: 96%